2015
DOI: 10.1111/1440-1681.12402
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of berberine on type 2 diabetic nephropathy in rats

Abstract: Inflammation, fibrosis, and lipid disorder are essential promoters in the pathogenesis of diabetic kidney injury in diabetes mellitus type 2. Berberine (BBR) has been reported to have beneficial effects on diabetic nephropathy, but its action mechanism is still unclear. The present study was designed to elucidate the therapeutic mechanism of BBR in a type 2 diabetic nephropathy rat model induced by a high-fat diet and low-dose streptozotocin injection. The diabetic rats were treated with or without BBR by gava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…Creatinine clearance (Ccr) was calculated using the following formula: Ccr (μl/min) = (Ucr/Pcr) × urine volume (μl/min), as P. Palsamy et al reported [22]. Albumin creatinine ratio (UACR) was expressed as the ratio of total urinary albumin to creatinine, as previously described [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Creatinine clearance (Ccr) was calculated using the following formula: Ccr (μl/min) = (Ucr/Pcr) × urine volume (μl/min), as P. Palsamy et al reported [22]. Albumin creatinine ratio (UACR) was expressed as the ratio of total urinary albumin to creatinine, as previously described [23]. …”
Section: Methodsmentioning
confidence: 99%
“…All samples were analyzed blindly for overall pathology using Image-Pro Plus software (Media Cybernetics, Warrendale, PA, USA). Immunohistochemistry and periodic-acid Schiff (PAS) staining of liver glycogen was performed as previously described (18). Briefly, the livers were fixed in 10% formalin and embedded in paraffin wax.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence demonstrates that BBR has multiple pharmacological activities, including as an antioxidant, anti-inflammatory, antilipemic, and hypoglycemic agent, indicating the clinical and research value of BBR as a promising therapeutic anti-DN drug in animals. 30 In addition, there is a substantial number of clinical reports in the Chinese literature regarding the antidiabetic action of BBR. 15 In diabetic patients, BBR in combination with other agents (e.g.…”
Section: Discussionmentioning
confidence: 99%